Employment and Migration Patterns of Recent Micrographic Surgery and Dermatologic Oncology Fellowship Graduates. Issue 7 (July 2021) - Kodumudi, Vijay; Hales, Hannah A.; Cohen, Jeffrey M.; Feng, Hao
Abstract : BACKGROUND: There is currently an uneven distribution of the Mohs surgery workforce, with a dearth in nonurban areas. The relationship between training and employment locations of Mohs surgeons has not been studied. OBJECTIVE: To analyze the employment location of recent micrographic surgery and dermatologic oncology (MSDO) graduates in reference to residency and fellowship locations. MATERIALS AND METHODS: Data collection of training and practice locations of 421 MSDO fellowship graduates from 2012 to 2017. RESULTS: Thirty-two percent ( n = 136) and 53% ( n = 225) of MSDO fellowship graduates' first employment locations were located within 10 and 100 miles of either their residency or fellowship locations. Ninety-six percent of graduates were employed in a metropolitan location. Female graduates worked closer to training sites than male graduates, with 62% ( n = 124) versus 46% ( n = 102) working within 100 miles of either training site. Analysis by fellowship census region showed that graduates clustered around training sites in all regions, with 45% to 60% of graduates working within 100 miles of either training site. CONCLUSION: The majority of graduates chose to work in a metropolitan area. Training location strongly predicts employment location. More than 45% of graduates in any region worked within 100 miles of their residency or fellowship site, and a sizeable portion worked within 10 miles.